2017
DOI: 10.1002/cncr.30511
|View full text |Cite
|
Sign up to set email alerts
|

The utility of abbreviated patient‐reported outcomes for predicting survival in early stage colorectal cancer

Abstract: Although most patients described good overall health and QOL and indicated that they were generally well supported, patients who experienced more pronounced fatigue or lacked emotional support had a higher likelihood of worse OS and DSS. These findings suggest that abbreviated PROs can inform and assist clinicians to identify patients who have a worse prognosis and may need more vigilant follow-up. Cancer 2017;123:1839-1847. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Within EC survivors, only very fatigued EC survivors showed a significant increased risk of all‐cause mortality. The found association in male CRC survivors is in line with the study of Hsu et al, which showed an association of fatigue with all‐cause mortality (HRadj = 1.76, 95% CI [1.34‐2.95]) in a stage II‐III CRC cohort. However, results in that study were not stratified by gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within EC survivors, only very fatigued EC survivors showed a significant increased risk of all‐cause mortality. The found association in male CRC survivors is in line with the study of Hsu et al, which showed an association of fatigue with all‐cause mortality (HRadj = 1.76, 95% CI [1.34‐2.95]) in a stage II‐III CRC cohort. However, results in that study were not stratified by gender.…”
Section: Discussionmentioning
confidence: 99%
“…But for colorectal cancer (CRC), studies reveal contradictory results. Two studies could not find an association between CRF with survival, whereas one showed an association . For endometrial cancer (EC), a univariate association between CRF and survival disappeared after adjustment for confounders .…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported that increased fatigue was associated with worse OS (HR 1.99; P=0.00007) and DFS (HR 1.63; P=0.03). 29 Poorer survival was also associated with increased age. No other study has evaluated the relationship between objectively measured cognitive function in patients with localised cancer with survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its usefulness as a patient-reported outcome, HRQL assessments provide can serve as predictors of future outcomes, such as prognosis and survival (Coates et al, 2000; Gotay et al, 2008; Hsu, Speers, Kennecke, & Cheung, 2017; Kaplan et al, 2007; Khouli et al, 2011; Terrin et al, 2015). However, evidence linking HRQL to future healthcare utilization, particularly in pediatric populations, has been limited (Kephart & Asada, 2009; Lima & Kopec, 2005; Parkerson et al, 2001; Ryan et al, 2013; Seid et al, 2004; Wherry, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%